The effectiveness of fiber-reinforced natural composites compared to the elastomer materials produced from nonrenewable resources in vibration transmission suppression. Issue 4 (December 2020) - Pawlik, Arkadiusz; Frackowiak, Stanislaw; Leluk, Karol
In this work, a number of tests were carried out to evaluate the effectiveness of the vibro-acoustic behavior composite consisting of a biodegradable polymer matrix (polylactid acid) and a filler in the form of natural flax fibers, with a moisture content of 2.03% after drying in 80°C for 4 h. To improve material dampening properties, polylactid acid was plasticized with polyethylene glycol 400 and triethyl citrate. The flax fiber content of the composite was 10, 20, and 30 wt%. Mechanical properties at bending and tensile were performed. For the measurement of vibro-acoustic suppression effectiveness, composite samples have been made to enable installation in the measurement system. The measuring system consisted of an unbalanced axial electric motor, resting on a steel frame placed on vibration suppressor. For comparison, the commercial grade vibration suppressor was used. In order to evaluate the vibration damping of the system by vibration suppressor, vibration engine frame vibration was forced by acceleration of the engine's rotational speed to specific frequencies. It has been proven that the type of the plasticizer used in the composite changes the vibro-acoustic suppression parameter. Also, the length and the weight percentage of the fibers result in lower material damping values.